Rare coexistence of spinal muscular atrophy with membranous nephropathy – A clinical conundrum with management dilemma - Gerry G. Mathew; Jayaprakash Varadharajan; Sreedhar Sailapathy; R. Kalpana (Indian Journal of Pathology and Microbiology)
A 48-year-old male presented with proximal muscle weakness of the shoulder with difficulty in lifting objects above the shoulder in July 2012. Electromyogram was suggestive of chronic motor axonal loss with a myogenic pattern, and a deltoid muscle biopsy revealed groups of atrophic muscle fibers and hypertrophic fibers with pan fascicular atrophy suggestive of adult-onset spinal muscular atrophy. He was managed conservatively and developed bilateral pedal edema in August 2022. He had nephrotic range proteinuria, and renal biopsy revealed capillary wall thickening of glomeruli with serum PLA2R antibody positivity suggestive of primary membranous nephropathy. He was managed with telmisartan for 6 months, and there was a reduction in proteinuria. In January 2023, he was given Injection Rituximab due to worsening proteinuria. He failed to have a clinical resolution. This case report describes the management dilemma in membranous nephropathy with SMA due to the risk of toxic myopathies associated with tacrolimus and steroids.